Factors affecting personal bankruptcy in Malaysia / Amira Izzati Zulkifle - Zulkifle, Amira Izzati (Faculty of Business and Management, 2019)
This study is to determine the Factors affects Personal Bankruptcy rates in Malaysia. There are five independent variables that have been select for this research. The independent variables are unemployment rate (UNR), non-performing loan (NPL), gross national income (GNI), household debt (HHD) and divorce rate (DVR). This study use the yearly data from 1985 until 2018 which total number of observation is 34 sample. Multiple linear regression model is applied to study the relationship between explanatory variables and explained variable. In this study, the results show two independent variables are significant, unemployment rate and divorce rate that influencing to Personal Bankruptcy rates in Malaysia except for non-performing loan, gross national income and household debt.